Addressing Failures in Achieving Hypertension Control in Low- and Middle-Income Settings through Simplified Treatment Algorithms - Jennifer Cohn; Helen Bygrave; Teri Roberts; Taskeen Khan; Dike Ojji; Pedro Ordunez (Ubiquity Press, 2022)
Hypertension is the most important risk factor for cardiovascular diseases (CVDs), which are the leading global cause of death. Hypertension is under-diagnosed and under-treated in most low- and middle-income countries (LMICs). Current algorithms for hypertension treatment are complex for the healthcare worker, limit decentralization, complicate procurement and often translate to a large pill burden for the person with hypertension. We summarize evidence supporting implementation of simple, algorithmic, accessible, non-toxic and effective (SAANE) algorithms to provide a feasible way to access and maintain quality care for hypertension. Implementation of these algorithms will enable task shifting to less specialised health care workers and lay cadres, provision of fixed dose combinations, consolidation of the market while retaining generic competition, simplification of laboratory requirements, and lowering costs for health systems and people who incur out of pocket expenses.